Fabrication system for surface modification of polystyrene beads by UV/Ozone treatment and its characterization - Ahmad Nor, Yusilawati; Mel, Maizirwan; Sopyan, Iis; Mohd. Salleh, Hamzah; Ng, K.H.; Wong, Chiow San (2009)
It is known that polystyrene must be chemically modified to make its surface enable to covalent cross-linking with protein. The aim of this study was to develop UV/Ozone treatment system and investigate the effects of treatment system on surface of polystyrene beads. The surface of polystyrene beads with an average size of 150μm was modified by UV/ozone treatment with or without distilled water at the same treatment time, ozone flow-rate and UV intensity. The treated beads were analyzed by ATR-FTIR to determine the introduction of carbonyl (-C=O) and carboxylic (COOH) onto the polystyrene surface. Sample characterization was also carried out by SEM, EDX and hydrophilicity test. The results show that there was an increased in hydrophilicity to the surface of polystyrene beads after the UV/ozone treatment and the introduction of carbonyl, carboxyl and hydroxyl groups on the polystyrene beads surface has been confirmed by ATR-FTIR result. This UV/Ozone treatment system for surfaces modification of PS beads was demonstrated to be effective for treatment of polystyrene bead and the best result has been obtained by UV/Ozone modification without distilled water.